Fabrication of fiber bragg grating with an apodised phase mask - Sulaiman Wadi Harun,; Prabakaran Poopalan,; Harith Ahmad, (Universiti Kebangsaan Malaysia, 2003)
A fiber Bragg grating (FBG) is fabricated with the aid of an apodised phase mask. The expanded Gaussian beam from a frequency doubled 244 nm CW argon ion laser is used as the UV printing source. A 66% reflectivity FBG was successfully fabricated by this method, however side lobes still appear in the short wavelength side of the spectrum. This condition is attributed to insufficient coverage by non-uniform ultraviolet light over the phase mask.